The Effects of a SFON-Based Early Numeracy Program on Multilingual Children's Early Numeracy and Oral Language Skills - Luomaniemi Katri; Mattinen Aino; McMullen Jake; Sorariutta Anne; Hannula-Sormunen Minna (Springer Publishing Company, 2023)
In this quasi-experimental study we examined how the Count How Many (CHM) intervention program can support multilingual children's early numeracy and oral language skills. The program is aimed at promoting spontaneous focusing on numerosity (SFON) and early numeracy skills in 3- to 5-year-old children who attend day care. We examined the effects of the CHM intervention with existing, but unanalyzed data, of16 multilingual children who participated in the intervention, which consists of 6 weeks of intensive training followed by a 5-month rehearsal phase. We matched two monolingual participants with each multilingual participant by age, SFON, and cardinality-related skills for each multilingual child. One of the matched children participated in the CHM intervention, while the other took part in an early literacy program, Let's Read and Talk. Children's early numeracy and oral language skills were measured at pretest, posttest, and delayed posttest. Multilingual children's SFON tendency, cardinality skills, number sequence production abilities, and story comprehension skills developed at a similar rate as monolingual participants during the follow-up period. The results suggest that it is possible to enhance SFON tendency and cardinality-related skills in multilingual children before school age. Furthermore, the time spent supporting early numeracy skills does not take away from language learning. However, more research is needed in larger populations to determine the applicability to broader segments of national and global societies.